Jumlah Tanggungan Sebagai Pemoderasi Pengaruh Pengalaman Usaha dan Pendapatan UMKM pada Kolektibilitas PKBL - Iswari, Anak Agung Widya Adi; Budiasih, I.Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 25 No 2 (2018)DO - 10.24843/EJA.2018.v25.i02.p12, 2018)
The Partnership and Community Development Program is one of the BUMN government programs that has an important role in providing capital assistance to UMKM. The purpose of this study is to determine the effect of business experience and income of SMEs toward the collectability of credit payment with household size as moderating variable in The PKBL Program at PT. Telkom, Tbk Witel Denpasar. Data were collected through unstructured interviews and questionnaire with saturated sample methods and obtains 163 respondents. D ata analysis technique used are Multiple Linear Regression Analysis and Moderated Regression Analysis (MRA). Based on the results showed that business experience and income of SMEs has a positive effect on collectability of credit payment . The results also show that the household size is able to increase the influence of business experience on collectability of credit , but the household size reduces the influence of income of SMEs on collectability of credit . Keywords: PKBL, business experience, income smes, household size, credit collectibility